Panelist Number III - Johnson, Howard (Academy of Management Journal, 1958)
Focuses on the learning process in the development of executives in a university program framework. Problem areas in the general area of university executive programs; Factors that characterize an effective executive development program; Information on the programs offered at the Massachusetts Institute of Technology in Cambridge.